2020
DOI: 10.1002/ente.202000457
|View full text |Cite
|
Sign up to set email alerts
|

Aging‐Optimized Fast Charging of Lithium Ion Cells Based on Three‐Electrode Cell Measurements

Abstract: The widespread adoption of battery electric vehicles (BEVs) is thought to be hindered mainly by the achievable driving range, the cost, and the lifetime of the batteries. In addition, longdistance travel with BEVs is commonly viewed as cumbersome and time consuming due to long recharging times. Many BEVs recently introduced by various manufacturers solve the problem of driving range with big battery packs with more than 70 kWh of energy capacity. This also allows higher absolute charging power as the relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Three-electrode cells can directly monitor electrode potentials in operando and have been used to inform the development of charging protocols that can avoid Li plating. The main limitation of such experiments is that they only approximate the true potentials experienced by the electrodes, especially at high charging currents . Electrode potentials are formally defined as the difference in electrical potential between the solid matrix and the electrolyte at a certain depth of the electrode; as such, it is characterized by a range of values at a given time, rather than a single potential. , Furthermore, design constraints require the reference probe to be placed at a finite distance away from the cathode and the anode, causing the sensed values of electrolyte potential to differ from that experienced at the working electrode .…”
mentioning
confidence: 99%
“…Three-electrode cells can directly monitor electrode potentials in operando and have been used to inform the development of charging protocols that can avoid Li plating. The main limitation of such experiments is that they only approximate the true potentials experienced by the electrodes, especially at high charging currents . Electrode potentials are formally defined as the difference in electrical potential between the solid matrix and the electrolyte at a certain depth of the electrode; as such, it is characterized by a range of values at a given time, rather than a single potential. , Furthermore, design constraints require the reference probe to be placed at a finite distance away from the cathode and the anode, causing the sensed values of electrolyte potential to differ from that experienced at the working electrode .…”
mentioning
confidence: 99%
“…Previous studies have shown how the anode potential can be used to perform charging protocols. [24][25][26][27][28][29] In contrast to a regular constant current constant voltage (CCCV) protocol, the CV phase is not adjusted to the cell voltage but to the reference potential (CV ref ). During the CC phase, a high C-rate can be applied until a fixed cut-off reference potential is reached.…”
Section: Charging Via Anode Potentialmentioning
confidence: 99%
“…The cell's negative electrode potential is monitored at various charge rates to prevent it from dropping below 0 V (vs Li/Li + ). Below this potential, lithium ions will preferentially gain electrons on the negative electrode surface and form a lithium plate [22,23,38]. Currently, the electroplating of a lithium metal layer on a copper wire surface is the most widely used and mature reference electrode preparation process for LIBs.…”
Section: Reference Electrode Implantation Activation and Stability Te...mentioning
confidence: 99%
“…There are also fast-charging strategies that rely on cell feedback and model simulations. Considering the relationship between lithium plating and the negative electrode potential of the cell, one approach involves implanting a reference electrode in the cell to measure the negative electrode potential and achieve fast charging without lithium plating by controlling this potential [22][23][24]. However, it is not feasible for real cells to constantly carry reference electrodes for negative electrode potential measurements in practical scenarios.…”
Section: Introductionmentioning
confidence: 99%